2003
DOI: 10.1258/002221503322113094
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of the auditory organ in trisomy 18 syndrome: human temporal bone histopathological study

Abstract: The purpose of this study was to define the histopathological changes in the temporal bone of a fetus with trisomy 18 syndrome, a stillborn due to perosplanchnia. Several anomalies were found including malformation of the auditory ossicles, residual mesenchyme in the middle ear, aberrant tensor tympani muscle, absence of stapedial tendon, aberrant lateral ampullary nerve and wide endolymphatic sinus. The incus body was deformed and separated from the long process by connective tissue and monocrural stapes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…Temporal bone CT assessments also revealed external and middle ear malformations in 89% of patients, supporting our findings that most of the patients had conductive or mixed HL, not sensorineural HL. In addition to our CT findings, Tadaki et al (2003) and Saito et al (1987) reported partial absence of the superior semicircular canal, enlargement of the endolymphatic duct sac, and abnormalities of the vestibule using temporal bone pathology of Trisomy 18 fetuses. In the cohort of the Hyogo Prefectural Kobe Children's Hospital, all nine patients underwent temporal bone CT showed external auditory canal atresia or stenosis (Tamaki et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
“…Temporal bone CT assessments also revealed external and middle ear malformations in 89% of patients, supporting our findings that most of the patients had conductive or mixed HL, not sensorineural HL. In addition to our CT findings, Tadaki et al (2003) and Saito et al (1987) reported partial absence of the superior semicircular canal, enlargement of the endolymphatic duct sac, and abnormalities of the vestibule using temporal bone pathology of Trisomy 18 fetuses. In the cohort of the Hyogo Prefectural Kobe Children's Hospital, all nine patients underwent temporal bone CT showed external auditory canal atresia or stenosis (Tamaki et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
“…Большинство аномалий носят спорадический характер, но примерно одна четверть случаев происходит в контексте генетического синдрома, синдрома Крузона, Клиппеля-Фейля, Пфейффера и других [5][6][7]. В случае отсутствия других аномалий решающую роль играет анамнез, и наиболее распространенным проявлением является ситуация, когда в поле зрения оториноларинголога попадает ребенок со снижением слуха, задержкой речи и плохой успеваемостью в школе, при минимальных отклонениях при отоскопии [8].…”
Section: ;20;1(110)unclassified
“…Most of the abnormalities are sporadic, but approximately one quarter of cases occur in the context of genetic syndrome, Crouzon syndrome, Klippel-Feil, Pfeiffer, and others [5][6][7]. In the absence of other anomalies, history plays a decisive role, and the most common manifestation is a situation when a child with hearing loss, speech delay and poor school performance, with minimal deviations during otoscopy, comes in view of the otorhinolaryngologist [8].…”
Section: ;20;1(110)mentioning
confidence: 99%